A assistência social às mulheres em situação de violência: a realidade dos CREAS em João Pessoa - Lopes, Nirleide Dantas (2018)
The purpose of this Master Dissertation is to understand social assistance to women in situations of violence in the city of João Pessoa-PB, based on the services of social protection of medium complexity offered at the Specialized Referral Centers of Social Assistance (CREAS). It aims to contribute to a more qualified service to the woman in a situation of violence, understanding such violence as an expression of the social question and that for this reason it should be treated as a public problem. It followed the proposal, considering the importance of providing emergency services to the needs of women, since the violence against this public has risen scarcely, as evidenced by the data on the map of violence (2015), which emphasizes women, revealing that the number of homicides against women in Paraíba grew 260% in ten years. When dealing with the theoretical methodological path, this research was adopted documentary research, carried out in the medical records of users of all CREAS, which attend to all rights violations. With regard to more specialized services, the provision of services to women and families at risk is limited to the provision of services to women in situations of violence, in view of the lack of a specific prevention, care and support service. women who have suffered or suffer some form of violence. The method of Marxian social theory was used to help interpret the situation of women in the present time. Finally, it is understood that although the municipality of João Pessoa has a network of assistance to women already consolidated, regarding the monitoring, support and guidance of women is insufficiently provided, since even with high rates of women killed in the capital the number of calls made by CREAS is small.